Measurements of Higgs boson production cross sections and couplings in the diphoton decay channel at root s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Dragicevic,M; Eroe,J; Del,Valle AE; Flechl,M; Fruehwirth,R; et al. (The Journal of High Energy Physics, 2021)
Measurements of Higgs boson production cross sections and couplings in events where the Higgs boson decays into a pair of photons are reported. Events are selected from a sample of proton-proton collisions at s√ = 13 TeV collected by the CMS detector at the LHC from 2016 to 2018, corresponding to an integrated luminosity of 137 fb−1. Analysis categories enriched in Higgs boson events produced via gluon fusion, vector boson fusion, vector boson associated production, and production associated with top quarks are constructed. The total Higgs boson signal strength, relative to the standard model (SM) prediction, is measured to be 1.12±0.09. Other properties of the Higgs boson are measured, including SM signal strength modifiers, production cross sections, and its couplings to other particles. These include the most precise measurements of gluon fusion and vector boson fusion Higgs boson production in several different kinematic regions, the first measurement of Higgs boson production in association with a top quark pair in five regions of the Higgs boson transverse momentum, and an upper limit on the rate of Higgs boson production in association with a single top quark. All results are found to be in agreement with the SM expectations.